Increased Bioactive Lipids Content in Human Subcutaneous and Epicardial Fat Tissue Correlates with Insulin Resistance - Błachnio-Zabielska, Agnieszka U.; Baranowski, Marcin; Hirnle, Tomasz; Zabielski, Piotr; Lewczuk, Anna; Dmitruk, Iwona; Górski, Jan (Lipids, 2012)
Obesity is a risk factor for metabolic diseases. Intramuscular lipid accumulation of ceramides, diacylglycerols, and long chain acyl-CoA is responsible for the induction of insulin resistance. These lipids are probably implicated in obesity-associated insulin resistance not only in skeletal muscle but also in fat tissue. Only few data are available about ceramide content in human subcutaneous adipose tissue. However, there are no data on DAG and LCACoA content in adipose tissue. The aim of our study was to measure the lipids content in human SAT and epicardial adipose tissue we sought to determine the bioactive lipids content by LC/MS/MS in fat tissue from lean non-diabetic, obese non-diabetic, and obese diabetic subjects and test whether the lipids correlate with HOMA-IR. We found, that total content of measured lipids was markedly higher in OND and OD subjects in both types of fat tissue (for all p < 0.001) as compared to LND group. In SAT we found positive correlation between HOMA-IR and C16:0-Cer ( r = 0.79, p < 0.001) and between HOMA-IR and C16:0/18:2 DAG ( r = 0.56, p < 0.001). In EAT we found a strong correlation between C16:0-CoA content and HOMA-IR ( r = 0.73, p < 0.001). The study showed that in obese and obese diabetic patients, bioactive lipids content is greater in subcutaneous and epicardial fat tissue and the particular lipids content positively correlates with HOMA-IR.